Induction of a Gradual, Reversible Morphogenesis of Its Host’s Epithelial Brush Border by Vibrio fischeri - Lamarcq, Laurence H. (American Society for Microbiology, 1998)
Bacteria exert a variety of influences on the morphology and physiology of animal cells whether they are pathogens or cooperative partners. The association between the luminous bacterium Vibrio fischeri and the sepiolid squid Euprymna scolopes provides an experimental model for the study of the influence of extracellular bacteria on the development of host epithelia. In this study, we analyzed bacterium-induced changes in the brush borders of the light organ crypt epithelia during the initial hours following colonization of this tissue. Transmission electron microscopy of the brush border morphology in colonized and uncolonized hosts revealed that the bacteria effect a fourfold increase in microvillar density over the first 4 days of the association. Estimates of the proportions of bacterial cells in contact with host microvilli showed that the intimacy of the bacterial cells with animal cell surfaces increases significantly during this time. Antibiotic curing of the organ following colonization showed that sustained interaction with bacteria is essential for the retention of the induced morphological changes. Bacteria that are defective in either light production or colonization efficiency produced changes similar to those by the parent strain. Conventional fluorescence and confocal scanning laser microscopy revealed that the brush border is supported by abundant filamentous actin. However, in situ hybridization with β-actin probes did not show marked bacterium-induced increases in β-actin gene expression. These experiments demonstrate that the E. scolopes-V. fischeri system is a viable model for the experimental study of bacterium-induced changes in host brush border morphology.